PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI PADA KELAS X SMA NEGERI 4 TANJUNGBALAI TAHUN AJARAN 2024/2025 - Putri, Sefrina; Mizkat, Eva; Nasution, Wan Nurul Atikah (Smart Education, 2025)
Abstract: Putri.Sefrina 2025. The Effect of the Discovery Learning Model on the Ability to Write Observation Report Texts at Xth Class Students of SMA Negeri 4 Tanjungbalai in 2025/2026 Academic Year. Skripsi. Indonesian Language and Literature Education Study Program, Faculty of Asahan University. Advisor: Eva Mizkat, S.S, M.Pd. The study aims to determine the effect of the Discovery Learning model on the ability to write observation report at Xth class students of SMA Negeri 4 Tanjungbalai. This study used an experimental method with a pretest-posttest control group design. The sample of this study were Xth class students divided into two groups: an experimental group using the Discovery Learning model and a control group using a conventional learning model. The results show that the Discovery Learning model had a positive effect on students' ability to write observation report texts. Students using the Discovery Learning model scored higher in writing observation report texts compared to students using the conventional learning model. This study demonstrates that the Discovery Learning model can improve students' ability to write observation report texts by facilitating students' independent discovery of concepts and information.Keywords: Discovery Learning, Writing Observation Report Texts, Writing Skills.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model Discovery Learning terhadap kemampuan menulis teks laporan hasil observasi siswa kelas X SMA Negeri 4 Tanjungbalai. Penelitian ini menggunakan metode eksperimen dengan desain pretest-posttest control group. Sampel penelitian ini adalah siswa kelas X SMA yang dibagi menjadi dua kelompok, yaitu kelompok eksperimen yang menggunakan model Discovery Learning dan kelompok kontrol yang menggunakan model pembelajaran konvensional. Hasil penelitian menunjukkan bahwa model Discovery Learning memiliki pengaruh positif terhadap kemampuan menulis teks laporan hasil observasi siswa. Siswa yang menggunakan model Discovery Learning memiliki skor yang lebih tinggi dalam menulis teks laporan hasil observasi dibandingkan dengan siswa yang menggunakan model pembelajaran konvensional. Penelitian ini menunjukkan bahwa model Discovery Learning dapat meningkatkan kemampuan menulis teks laporan hasil observasi siswa dengan cara memfasilitasi siswa untuk menemukan konsep dan informasi secara mandiri.Kata Kunci: Discovery Learning, Menulis Teks Laporan Hasil Observasi, Kemampuan Menulis.